High-field/high-frequency EPR spectroscopy in protein research: principles and examples - Möbius, Klaus; Savitsky, Anton (Technische Universität Dortmund, 2022)
During the last decades, the combined efforts of biologists, chemists, and physicists in developing high-field/high-frequency EPR techniques and applying them to functional proteins have demonstrated that this type of magnetic resonance spectroscopy is particularly powerful for characterizing the structure and dynamics of stable and transient states of proteins in action on biologically relevant time scales ranging from nanoseconds to hours. The review article describes how high-field EPR methodology, in conjunction with site-specific isotope and spin-labeling strategies, is capable of providing new insights into fundamental biological processes. Specifically, we discuss the theoretical and instrumental background of continuous-wave and pulse high-field EPR and the multiple-resonance extensions EDNMR, ENDOR, TRIPLE, ESEEM, PELDOR, and RIDME. Some emphasis is placed on a balanced description of both the historical spadework and the achieved performance of advanced EPR at 95 GHz and 360 GHz. This culminates in a coherent treatment of state-of-the-art research of high-field EPR in terms of both instrumentation development and application to representative protein complexes such as cofactor binding sites in photosynthesis.
Applied magnetic resonance;54(2)
Keywords: 530